Excited electronic structure of methylcyanoacetylene probed by VUV Fourier-transform absorption spectroscopy. (October 2016) - Lamarre, N.; Gans, B.; Vieira Mendes, L.A.; Gronowski, M.; Guillemin, J.-C.; De Oliveira, N.; Douin, S.; Chevalier, M.; Crépin, C.; Kołos, R.; Boyé-Péronne, S.
Abstract: High resolution photoabsorption spectrum of gas-phase methylcyanoacetylene ( CH 3 C 3 N ) has been recorded from 44 500 to 130 000 cm −1 at room temperature with a vacuum ultraviolet Fourier-transform spectrometer on the DESIRS synchrotron beamline (SOLEIL). The absolute photoabsorption cross section in this range is reported for the first time. Valence shell transitions and Rydberg series converging to the ground state X ˜ + E 2 of the cation as well as series converging to electronically excited states ( A ˜ + A 1 2 and C ˜ + ) are observed and assigned. Time-dependent density-functional-theory calculations have been performed to support the assignment of the experimental spectrum in the low energy range. A tentative scaling of the previously measured CH3 C3 N + ion yield by Lamarre et al.[17] is proposed, based on the comparison of the absorption data above the first ionization potential with the observed autoionization structures. Abstract : Highlights: We report the first photoabsorption spectrum of CH 3 C 3 N in the VUV spectral range. The absolute VUV photoabsorption cross section of methylcyanoacetylene is measured. Assignment of valence transitions and Rydberg series is supported by calculations. Absolute scaling of the CH 3 C 3 N + ion yield is deduced by comparison with the absorption data.